EVALUATION OF SF6 GAS QUALITY TEST AT THE 150 KV KALIBAKAL SUBSTATION - Saefurrohman, Asep; Mubarok, Rizky; Mubarok, Fachruroji (Journal of Electronic and Electrical Power Applications, 2025)
Electricity has become a primary necessity in modern life, and the substation functions as a pivotal hub for its distribution from the source to the customer. This critical infrastructure is equipped with vital equipment such as PMT (Power Breakers), which play a crucial role in ensuring system reliability. The PMT serves dual functions as both a breaker and a connecting switch, handling anomalies or network repairs efficiently. However, PMT operations frequently involve arcs, which have the potential to damage equipment. To mitigate this risk, SF6 insulating gas is employed to effectively extinguish arcs, ensuring the safety and reliability of the electrical network. Routine testing is imperative to ensure the efficacy of SF6 gas, encompassing assessments of purity, dew point, and decomposition products. The present study was conducted over a period of two months at the 150kV Kalibakal Substation. The research method incorporated field observation, a comprehensive review of existing literature, and rigorous SF6 gas testing procedures.The study's findings revealed that the average purity of SF6 gas exceeded 97%, the presence of decomposition products of SO2 was absent, and the dew point was recorded to be less than -5°C. Additionally, the SF6 gas pressure at Bay bumiayu 1 and bumiayu 2 remained within safe limits, exceeding 6.4 bar.A significant decrease in pressure could potentially compromise the functionality of the PMT, as it was observed that the PMT operates optimally at pressures above the nominal value. However, at pressures below the nominal value, the performance of the PMT is compromised, leading to malfunctions in the arc fire extinguisher and potentially causing equipment damage and endangering human safety. The findings indicate that the condition of SF6 gas is stable and safe for substation operations.